Wind-driven mixing causes a reduction in the strength of the continental shelf carbon pump in the Chukchi Sea ... - Hauri, Claudine; Winsor, Peter; Juranek, Laurie W.; McDonnell, Andrew M. P.; Takahashi, Taro; Mathis, Jeremy T. (Columbia University, 2013)
The Chukchi Sea is thought to be a globally important sink of atmospheric CO2 due to the summertime drawdown of surface pCO2 by phytoplankton and subsequent shelf-to-basin transport of CO2-enriched subsurface waters into the upper halocline of the Arctic Ocean. Here we show that annually occurring storm-induced mixing events during autumn months disrupt water column stratification and stir up remineralized carbon from subsurface waters to the surface, leading to CO2 outgassing to the atmosphere. Our analysis provides a new understanding of the dynamics of carbon cycling in the region and suggests that late season wind events are strong and frequent enough to significantly decrease the carbon sink strength of the Chukchi Sea on a scale of relevance to the global carbon cycle. These results highlight the importance of obtaining data with more complete seasonal and spatial coverage in order to accurately constrain regional to basin-scale carbon flux budgets. ...